2015
DOI: 10.1007/s11764-015-0442-2
|View full text |Cite
|
Sign up to set email alerts
|

Telephone, print, and Web-based interventions for physical activity, diet, and weight control among cancer survivors: a systematic review

Abstract: Broad-reach lifestyle interventions are effective, with further research needed to evaluate their generalizability and integration into cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
137
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 79 publications
4
137
0
1
Order By: Relevance
“…The behavioral and health-related fitness improvements in the CHALLENGE Trial are especially noteworthy given that the intervention was delivered over a 1-year period by over 100 different PACs from 42 centers in two countries. The vast majority of exercise interventions in cancer survivors have assessed short-term behavioral changes (<6 months) in a limited number of centers (5,6). Moreover, the small number of trials that have included longer term follow-up and broader implementation have often produced the smallest behavioral and fitness changes (5, 6), highlighting the well-known trade-off between reach/feasibility and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavioral and health-related fitness improvements in the CHALLENGE Trial are especially noteworthy given that the intervention was delivered over a 1-year period by over 100 different PACs from 42 centers in two countries. The vast majority of exercise interventions in cancer survivors have assessed short-term behavioral changes (<6 months) in a limited number of centers (5,6). Moreover, the small number of trials that have included longer term follow-up and broader implementation have often produced the smallest behavioral and fitness changes (5, 6), highlighting the well-known trade-off between reach/feasibility and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, exercise interventions to improve cancer outcomes will likely require substantial and sustained behavior change. Unfortunately, exercise interventions delivered through practical avenues such as telephone counseling, print materials, and web-based programs often induce only small behavioral changes that are unlikely to improve cancer outcomes (5,6). Conversely, exercise interventions delivered through optimal avenues such as fully supervised programs by qualified professionals often induce larger behavioral changes as well as healthrelated fitness improvements (7,8); however, their potential for large-scale dissemination is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several well-designed randomized controlled trials have demonstrated distance-based approaches to facilitating PA behavior among breast cancer survivors are effective (16,(27)(28)(29). One recent review of telephone, print, and web-based interventions for PA concluded that broad-reach intervention delivery modalities are effective for improving health behaviors, including PA (30). However, most studies only included survivors who had completed active treatment (with most being !1 year post diagnosis).…”
Section: Discussionmentioning
confidence: 99%
“…Goode, Lawler, Brakenridge, Reeves, and Eakin (2015), in a systematic review on telephone, print, and Web-based interventions for physical activity, diet, and weight control among cancer survivors, suggest the integration of other technologies such as SMS and mobile/smartphone applications. This includes exploration of the potential of these technologies to deliver long-term support in a more cost-effective way.…”
Section: Assessment Toolsmentioning
confidence: 99%